NANOCOVERING OF TITAN WITH SILICON AND MOLYBDENUM AS ACTIVATOR OF FORMATION AND REACTIONARY AGGLOMERATION OF FILTERS AND MEMBRANES - V. N. Kovalevski; Yu. G. Alekseev; A. V. Kovalevskaya; A. E. Zhuk (Литьë и металлургия)
The technology of production of porous powder materials with frame structure on the basis of spherical particles of titan powder by means of applying on them technological coverings (Si + Mo) + C with the thickness up to 2 mm is developed. Formation of powders with covering was carried out in the mold at pressure below yield point (up to 150 MPa).